Comprehensive analysis of LRRC42 as a potential biomarker and key cellular processes in cancer development - Rongfu Huang; Jianfeng Yao; Lei Liu; Hua Li; Baoshan Huang (Scientific Reports)
Abstract This study investigated the role of LRRC42 in tumor development and progression using comprehensive methodologies. Analysis of RNA-seq data from the TCGA database revealed that LRRC42 expression is upregulated in various tumor tissues, including bladder cancer (BLCA), breast cancer (BRCA), cholangiocarcinoma (CHOL), colorectal cancer (COAD), esophageal cancer (ESCA), glioblastoma (GBM), head and neck squamous cell carcinoma (HNSC), liver hepatocellular carcinoma (LIHC), lung adenocarcinoma (LUAD), and skin cutaneous melanoma (SKCM), compared to normal tissues. Conversely, LRRC42 was significantly downregulated in kidney chromophobe (KICH) and thyroid carcinoma (THCA) tissues. Single-cell analysis using the TISCH2 database highlighted high LRRC42 expression levels in specific subpopulations across different cancers. Correlation analyses indicated associations between LRRC42 expression and prognosis in multiple tumors, linking it to poor overall survival in several cancer types. Investigations into LRRC42’s interactions with the tumor immune microenvironment and signaling pathways demonstrated significant correlations with immune cells, epithelial-mesenchymal transition molecules, autophagy-related factors, and pyroptosis-related molecules. Focusing on LRRC42’s potential role in hepatocellular carcinoma (HCC), the study uncovered co-expression relationships with Th2 cells and identified genes enriched in mRNA processing and cell cycle regulation pathways. Functional validation through LRRC42 knockdown experiments revealed its critical involvement in promoting cell proliferation, migration, and invasion in HCC cell lines. Collectively, these findings emphasize LRRC42 as a promising therapeutic target for inhibiting HCC progression and suggest its pivotal role in modulating key cellular processes integral to HCC advancement.